Three Gorges Dam Project: An Introduction - Acharya, Pranav (Hydro Nepal: Journal of Water, Energy and Environment, 2008)
The Three Gorges Dam Project (TGDP) on the Yangtze River in Hubei Province is touted as the long term solution to China’s increasing energy and agricultural needs. TGDP, with a 1084 km2 reservoir of 39.3 billion m3 capacity, will be the largest multipurpose water conservancy project ever built in the world. The main structures of the project are dam, hydropower stations and navigation facilities. After studying fifteen alternative sites and approval of Environmental Impact Statement (EIS) in February 1992, the construction of the dam began in 1994 with an expected duration of 17 years. Annual reduction of 40-50 million tons of coal consumption by providing 85 billion kilowatt hours of electricity, protection of 1.6 million hectares of agricultural land from floods and considerable improvement of navigation and tourism sector are the major anticipated benefits of TGDP. However, the proposed benefits put significant pressure on ecological and socio-cultural environment of the TGDP area. Relocation and resettlement of over 1.3 million local populations, inundation of several sites of historical importance, deforestation and loss of biodiversity including several endangered species of flora and fauna across a region of 58,000 km2, increased sedimentation, water pollution and potential earthquake risks are the major adverse consequences of TGDP.Key words: Three Gorges Dam Project (TGDP), environmental impacts, alternatives, resettlement, biodiversity, ecology, ChinaHydro Nepal: Journal of Water, Energy and Environment Vol. I, Issue No. 1 (2007) pp. 54-56